PERAN ESTETIKA SENSORIK DALAM PRAKTIK MEDIA ART: ANALISIS PAMERAN FOTOGRAFI RUANG PUBLIK KOTA MALANG: THE ROLE OF SENSORY AESTHETICS IN MEDIA ART PRACTICES: AN ANALYSIS OF A PUBLIC SPACE PHOTOGRAPHY EXHIBITION IN MALANG CITY - Ahmad Zakiy Ramadhan; Sunarmi (Fakultas Seni Rupa dan Desain, Universitas Trisakti, 2025)
This study aims to analyze the role of sensory aesthetics in a public space photography exhibition as a form of media art practice that supports the city branding of Malang City. The exhibition was held during the Ngalam Culture Festival at Kampung Skabrom and integrates visual experiences, the environment, and social interactions that engage visitors in creating perceptions of the city's identity. Using a qualitative approach with a case study design, data were collected through semi-structured interviews, participatory observation, and visual documentation. The results show that sensory aesthetic experiences involving sight, hearing, and social interactions play a crucial role in strengthening visitors' emotional attachment and connection to the city. The findings reveal four main themes: historical atmosphere, visual sensory aesthetics, community sound, and representation of the city's identity. This research contributes to expanding the theory of city branding based on sensory experiences and emphasizes the importance of public art in creating inclusive and participatory city narratives. The study also provides recommendations for creative city planning that involves public participation through media art in public spaces.